Origin and temporal variability of unusually low δ13C-DOC values in two High Arctic catchments - Hindshaw, R.S.; Lang, S. Q.; Bernasconi, Stefano M.; id_orcid:0 000-0001-7672-8856; Heaton, T.H.E.; Lindsay, M.R.; Boyd, E.S. (Journal of Geophysical Research: Biogeosciences, 2016)
ISSN:0148-0227 ISSN:2169-8953 ISSN:2169-8961